Providing a development model for the effectiveness of persuasive advertising in social networks - Hamzeh Hessani Khabr; Payam Paslari; Mehdi Bagheri; Saeed Muradpour (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe purpose of this research is to provide a development model for the effectiveness of persuasive advertising in social networks. The research method is applicable in terms of its purpose and qualitative in terms of implementation. The statistical population of the research includes 15 experts, university professors, and managers and specialists in the field of marketing; selected through the maximum diversity sampling method. A semi-structured interview was used to collect information. Data-based and coding method was used for data analysis. In open coding, the researcher found 146 concepts, which were classified into 31 categories. Persuasive advertising in social networks can have significant effects on the behavior and attitude of consumers. These effects include changes in consumer behavior, intensification of competition, formation of values ​​and beliefs, influence on decision making, change in social behavior, influence on brand trust, change in brand attitude, and influence on social networks. However, these effects depend on various factors such as technological changes, social and cultural changes, economic changes, legal and political changes, changes in competition, and changes in the content and format of advertisements. As a result, to increase the effectiveness of persuasive advertising in social networks, it is recommended to pay special attention to these factors.Extended Abstract                                           IntroductionOne of the most important and biggest changes occurred in the field of human life is the emergence of virtual social networks on the Internet. Almost all thinkers share the same opinion that social media has changed and influenced the lifestyle and human life, although there are different views about the nature, intensity and type of these effects (Keshvariyan et al, 2019). The majority of marketing managers believe that virtual social media are primarily used for "brand building and brand awareness" activities, and evidence from academic studies suggests that effective use of social media helps improving brand awareness and brand image, and ultimately the awareness of the product and services and even improvement of the financial performance of the brands (Godey et al, 2016). The ultimate goal of advertising is to convince consumers to change their attitude towards the advertised product or service. Previous studies in the field of advertising showed that attitude towards advertising affects brand attitude and purchase intention through a hierarchy of effects. Therefore, attitude is an important factor that can predict the effectiveness of advertising. In general, attitudes are mental states by which people understand their environment and react to it (Eisend, 2021). Preliminary investigations show that many advertising companies that produce content on Instagram still use old models for measuring the effectiveness of their ads, such as the Aida and Dagmar models. Meanwhile, the Instagram environment is very different compared to traditional media, and this difference leads to differentiation in measuring the effectiveness of advertising (Abdulhosseini et al, 2019). Finally, this research also answers the main question: How to provide a development model for the effectiveness of persuasive advertising in social networks?Theoretical FrameworkAdvertisementsAdvertising is the release of information utilized to promote products to consumers. Based on the distribution channels, advertisements are classified into offline and online advertisements. Offline advertising is non-internet-based advertising, including television, radio, and print advertising. While online advertising uses the Internet to disseminate product information, such as online display advertising, search advertising, and email advertising. Advertising has many economic benefits, including increased product sales, increased firm performance and value, and improved market efficiency, which have received considerable research attention (Bayer et al, 2020).Social NetworksSocial networks are a new generation of sites and bases that operate on the Internet and by using a search engine and adding features such as chat, electronic messaging, image and sound transmission, bring together a group of Internet users with special characteristics and provide the possibility of more communication of users in the form of a network of individual and group relationships and finally, these users can share content (share and express their interests, thoughts and activities) with others users (Jaffali, 2019).Saghafian et al, (2024) investigated the presentation of the model of customer participation with brands in social networks with emphasis on cultural differences. The results of the quantitative section show that the dimensions and components of customer engagement with brands have an impact on social networks with an emphasis on cultural differences. Also, the results show a strong and very good fit of the model.Torki et al, (2023) investigated the impact of social media participation on green management (case study of employees of Shahrekord industrial companies). The results showed that the amount of use of social media, the type of use of social media, and the amount of trust in users in social media have a positive effect on green management. This means that the Internet has become an inseparable part of life because of people's easy access to virtual space and social networks. In order to make optimal use of the created space, companies are trying to use this opportunity optimally and to their advantage and improve the green management.Motiei (2023) examined the presentation of a model for advertising persuasion strategy with nationalism approach in national media. In the current research, a paradigm model is presented, the main focus of which is persuading the national media in order to promote national production. Based on the obtained results, "national and organizational consensus", "geographical requirements" and "economic growth" are three important features of supporting domestic production, which were realized if supported by institutions including the Broadcasting Organization. In this research, the paradigm model of persuasion of commercial advertisements was formulated with the approach of promoting national production and specifically, in the national media. The research model consists of 10 main categories, the main axis of which is the persuasion of the national media in order to promote national production. In this model, the causal conditions include four categories of assistance to the domestic economy, geographical requirements, national and organizational consensus. Also, three strategies were chosen to achieve the goal of the research, which are: economic efficiency, management tactics, and security.Research methodologyThe research method is applicable in terms of its purpose and qualitative in terms of implementation. The statistical population of the research includes 15 experts, university professors, and managers and specialists in the field of marketing; selected through the maximum diversity sampling method. A semi-structured interview was used to collect information. Research findingsData-based and coding method was used for data analysis. In open coding, the researcher found 146 concepts, which were classified into 31 categories. Persuasive advertising in social networks can have significant effects on the behavior and attitude of consumers. These effects include changes in consumer behavior, intensification of competition, formation of values ​​and beliefs, influence on decision making, change in social behavior, influence on brand trust, change in brand attitude, and influence on social networks. However, these effects depend on various factors such as technological changes, social and cultural changes, economic changes, legal and political changes, changes in competition, and changes in the content and format of advertisements. As a result, to increase the effectiveness of persuasive advertising in social networks, it is recommended to pay special attention to these factors.ConclusionThe current research was conducted with the aim of providing a development model for the effectiveness of persuasive advertising in social networks. The results of this research are in agreement with the results of Saghafian et al, (2024), Torki et al, (2023), Motiei (2023), Ghiasian et al, (2021), Ahadi & Ghasemi (2020), Balazadeh (2020), Abdulhosseini et al, (2019), Haque Beg et al, (2019), and Gordon et al, (2019). Abdulhosseini et al, (2019) showed that to measure the effectiveness of advertising on Instagram, it is possible to emphasize four dimensions, including dimensions related to advertising, dimensions related to psycho-biological effects, dimensions related to the brand, and dimensions related to the media. Each of these dimensions includes different components that researchers have confirmed the relationship between them and the effectiveness of advertising on Instagram.According to the results of the research, the following suggestions are presented:Clothing companies such as Hakobian, LC Man, Maxim, and Ikat can use persuasive techniques such as "social validation" or "reason seeking" in their social media advertising. One of the implementation ways is that these companies can share pictures or videos of real customers wearing the clothes of these brands on their social networks. This not only creates "social validation", but also gives customers a sense of confidence that others are also satisfied with these brands' products. In this way, companies can benefit from the principles of persuasion to increase the effectiveness of their advertisements in social networks.